2019
DOI: 10.1002/jcb.28630
|View full text |Cite
|
Sign up to set email alerts
|

Identification of potential key genes associated with osteosarcoma based on integrated bioinformatics analyses

Abstract: Due to high rates of metastasis and poor clinical outcomes for patients, it is important to study the pathomechanisms of osteosarcoma. However, due to the fact that osteosarcoma shows significant interindividual variation and high heterogeneity, the identification of differentially expressed genes (DEGs) at the population level cannot answer many important questions related to osteosarcoma tumorigenesis. Therefore, a new strategy to identify dysregulated genes in osteosarcoma samples is required. The aim of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…In the present scenario, the integration of high-throughput omics technology and bioinformatics analysis continues to be a significant and effective research method in clinical research to discover target molecules associated with diseases. Moreover, it is considered to be a reliable technique for bioinformatics analysis of the integration of a huge quantity of omics data to discover targets that have potential application importance, for instance, researches on colorectal cancer (Luca et al, 2019), oral cancer (Di et al, 2019;Pan et al, 2019), ovarian cancer (Hu et al, 2019), osteosarcoma (Ma et al, 2019), and lung cancer (Feng et al, 2019). In the present study, the first step we did was to collect expression profiles of NSCLC mRNA from the GEO database and inspected them for genes that are commonly differentially expressed.…”
Section: Introductionmentioning
confidence: 99%
“…In the present scenario, the integration of high-throughput omics technology and bioinformatics analysis continues to be a significant and effective research method in clinical research to discover target molecules associated with diseases. Moreover, it is considered to be a reliable technique for bioinformatics analysis of the integration of a huge quantity of omics data to discover targets that have potential application importance, for instance, researches on colorectal cancer (Luca et al, 2019), oral cancer (Di et al, 2019;Pan et al, 2019), ovarian cancer (Hu et al, 2019), osteosarcoma (Ma et al, 2019), and lung cancer (Feng et al, 2019). In the present study, the first step we did was to collect expression profiles of NSCLC mRNA from the GEO database and inspected them for genes that are commonly differentially expressed.…”
Section: Introductionmentioning
confidence: 99%
“…In addition CD74 can act as a receptor for macrophage migration inhibitory factor (MIF). It was found that MIF inhibited osteoclast formation and CD74 knockout (KO) mice had decreased bone mass[23]. We detected the CD74 and CTSK co-expression in OCs by IHC method on serial section.…”
Section: Resultsmentioning
confidence: 99%
“…Currently, there are no effective biomarkers or commercial tests for early diagnosis of UC in clinical practice. The bioinformatics analysis has been widely used for exploring the molecular mechanisms of various diseases [ 5 7 ], which contribute to identify novel biomarkers able to improve both diagnostic and prognostic strategies of UC.…”
Section: Introductionmentioning
confidence: 99%